2018
DOI: 10.3389/fpsyg.2018.00642
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Parental Control and Parent-Child Relational Qualities on Adolescent Internet Addiction: A 3-Year Longitudinal Study in Hong Kong

Abstract: This study investigated how parental behavioral control, parental psychological control, and parent-child relational qualities predicted the initial level and rate of change in adolescent internet addiction (IA) across the junior high school years. The study also investigated the concurrent and longitudinal effects of different parenting factors on adolescent IA. Starting from the 2009/2010 academic year, 3,328 Grade 7 students (Mage = 12.59 ± 0.74 years) from 28 randomly selected secondary schools in Hong Kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
77
6
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 50 publications
(84 reference statements)
11
77
6
3
Order By: Relevance
“…The results of the few prospective studies were generally in line with those of the cross-sectional investigations. More prospective studies are needed, with random sampling and with assessments covering three or more follow-up years, as has been done by the research groups of Chng and Shek (Chng et al, 2015;Shek, Zhu, & Ma, 2018). Reliable and valid questionnaires should be designed to measure parental mediation and family cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the few prospective studies were generally in line with those of the cross-sectional investigations. More prospective studies are needed, with random sampling and with assessments covering three or more follow-up years, as has been done by the research groups of Chng and Shek (Chng et al, 2015;Shek, Zhu, & Ma, 2018). Reliable and valid questionnaires should be designed to measure parental mediation and family cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al's meta-analysis, involving 686,672 children and adolescents, revealed that the aggregate lifetime and 12-month prevalence rates of suicide attempts, suicidal plans, suicidal ideation, non-suicidal self-injury, and deliberate self-harm were 4.5%, 7.5%, 14.2%, 19.5%, and 14.2% in adolescents, respectively [2]. In addition, internet addiction, gaming problems, pathological gambling, and social media addiction have rapidly increased in recent decades [3][4][5]. UNICEF warned that one-fifth of adolescents in the world have mental health problems, which could hinder adolescent adjustment and create unfavorable consequences in adulthood [6].…”
Section: Introductionmentioning
confidence: 99%
“…According to existing literature, restriction and control are associated with negative outcomes, while parental monitoring promotes healthy and positive psychological development [38]. With respect to internet use, the adequate monitoring of an adolescent´s whereabouts and the strategies of behavioural control have been linked to lower levels of EIU [39,40], while intrusive parental control and autonomy restriction are likely to manifest as risk factors for EIU [41].The present overview suggests that family environmental factors might play an important role in moderating internet use in adolescence. However, to our knowledge, none of the available studies have comprehensively examined these factors in relation to EIU.…”
mentioning
confidence: 99%